The hugot that is Kimi No Nawa a review of and reflection on the success of Your Name (2016) in the Philippines - Luczon, Nef T. (2019)
Access online through this link: https://www.plarideljournal.org/article/the-hugot-that-is-kimi-no-nawa-a-review-of-and-reflection-on-the-success-of-your-name-2016-in-the-philippines
Keywords: Your Name (film); Shinkai, Makoto; Film reviewing